Edukasi Pola Makan Sehat kepada Pasien Peserta Prolanis Di Puskesmas Trosobo Sidoarjo - Nisyak, Khoirun; Amanda, Eviomitta Rizki; Prasetya, Yulianto Ade; Nurdianto, Arif Rahman; Hisbiyah, A’yunil (DHARMA BAKTI, 2021)
Participants of the Chronic Disease Management Program (PROLANIS) at the Trosobo Health Center are a group of patients with diabetes mellitus and hypertension whose condition needs to be monitored regularly. Diet is one of the important factors that affect the stability of the health condition of patients in the Prolanis group. The purpose of this program is to provide education on healthy eating patterns for Prolanis participants. The method of activities carried out is counseling and workshops with a total of 30 patients. Counseling activities and workshops are carried out by involving families who care for patients. Evaluation of the success of the program is determined by the patient's level of understanding about healthy eating patterns and fasting blood sugar levels and the patient's blood pressure to normal and stable levels over time. Based on the results of the program evaluation that has been carried out, 90% of Prolanis patients understand about healthy eating patterns and apply them in their daily lives.